Active Power Management for PV Systems under High Penetration Scenario - Fernando Medina; Nimrod Vazquez; Joaquín Vaquero; Jaime Arau; Leonel Estrada; Elso Rodriguez (International Journal of Photoenergy)
Although PV systems are one of the most widely used alternatives as a renewable energy source due to their well-known advantages, there are significant challenges to address related to voltage fluctuations and reverse power flow caused by high PV penetration scenarios. As a potential solution to this problem, an active power management strategy is proposed in this work using a residential cluster as a benchmark. The proposed strategy is analyzed and experimentally verified, offering a simple way to reduce the voltage fluctuations by regulating the active power delivered by the PV system, achieving also relevant functionalities for the system, such as the regulation of the DC bus voltage, maximum power point tracking (MPPT), synchronization with the grid voltage, detection of high penetration conditions, and a simple strategy for the main controller with an effective performance. The proposal system shows satisfactory results being able to maintain grid voltage fluctuations within the voltage standard specifications.